Manajemen risiko reputasi pada perbankan syariah di era digital: tantangan, strategi mitigasi, dan kepatuhan syariah - Dzakirah, Nabilah Mutiara (Maliki Interdisciplinary Journal, 2025)
This study analyzes reputation risk management in Islamic banking in Indonesia in the context of the digital era. Using a qualitative approach through literature study, this study aims to identify the characteristics of reputation risk, the factors that influence it, and effective mitigation strategies for Islamic banking. The results of the study indicate that reputation risk in Islamic banking has a more complex dimension than conventional banking, because it is closely related to sharia compliance and the expectations of Muslim customers. The digital era has presented new challenges in the form of rapid dissemination of information through social media, high transparency, and cybersecurity. Effective mitigation strategies include strengthening the governance system, implementing sharia-compliant digital technology, increasing employee digital literacy, and developing proactive communication with stakeholders. This study recommends the development of a reputation risk management framework that is integrated with the sharia compliance system to maintain customer trust and the stability of the Indonesian Islamic banking industry.